Skala Ekonomis Industri Tas Kain di Kota Denpasar - Parama Putra, Anak agung Ngurah; Jember, Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 12, Desember 2013 (pp. 547-569), 2013)
Development of the industrial sector in Bali each year have significant growth, one of which is a cloth bag industry.  Cloth bags in many industries due to Denpasar Denpasar is the capital and center for domestic and international tourism destination. In general industrial cloth bag in Denpasar have several constraints such similar industries who have a strong capital still dominates in the process of marketing and production processes, intense competition, and the use of labor is not optimal, highly influential on production. This study aims to evaluate the performance of industrial cloth bag, knowing the nature of economies of scale and industrial production of cloth bags in the city of Denpasar. The analysis technique used is multiple linear regression with the transformation of the Cobb – Douglas models. The results showed, that the industrial economies of scale in Denpasar cloth bags are increasing returns to scale. Nature fabric bag production is labor-intensive. Partial and simultaneous labor and capital significantly influence industrial production of cloth bags in the city of Denpasar.
Keywords: fabric bag production; labor and capital